E3 ubiquitin ligases regulating plant stress responses: an overview - Guerra D.; Mastrangelo A.M.; Cattivelli L.; Mazzucotelli E. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Post-translational modifications are emerging as a key regulatory component of many important cellular mechanisms. Among these ubiquitination, a multistep reaction, sequentially involving three enzymes named E1, E2 and E3, labels proteins with ubiquitin and led to 26S-mediated degradation. Protein ubiquitination plays a key role in a wide variety of cellular processes such as hormone signaling, DNA repair, biotic and abiotic stress response, cell cycle regulation to name few. In Arabidopsis more than one thousands of genes code for E3 ubiquitin ligase enzymes that specifically recognise target proteins. This suggests that a large amount of targets might be regulated by ubiquitination.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)